The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1080/21870764.2020.1789287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cr3+, Co2+ and Cu2+ on the formation of calcium silicates hydrates under hydrothermal conditions at 200 °C

Abstract: This work aims to investigate the influence of Cr 3+ , Co 2+ and Cu 2+ on the formation of calcium silicates hydrates in CaO-SiO 2-Al 2 O 3-H 2 O system under hydrothermal conditions. The dry primary mixture with the molar ratio CaO/(SiO 2 + Al 2 O 3) = 1.5 and Al 2 O 3 /(Al 2 O 3 + SiO 2) = 0.05 was mixed with heavy metal nitrate solutions (metal ions concentration-10 g/l) to reach the water/solid ratio of the suspension equal to 10.0. The hydrothermal synthesis was carried out in unstirred suspensions, under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previously it has been shown that hydrothermal C -S -H phases may incorporate heavy metal elements [58]. That Cr and V are effectively incorporated in the reaction products that formed during autoclaving is also proven by the composition of the PARC reaction product (Table 5).…”
Section: Leaching Analysis Of the Autoclaved Materialsmentioning
confidence: 78%
“…Previously it has been shown that hydrothermal C -S -H phases may incorporate heavy metal elements [58]. That Cr and V are effectively incorporated in the reaction products that formed during autoclaving is also proven by the composition of the PARC reaction product (Table 5).…”
Section: Leaching Analysis Of the Autoclaved Materialsmentioning
confidence: 78%